The Fathers of the Constitution: A Chronicle of the Establishment of the Union - Farrand, Max, 1869-1945; Johnson, Allen, 1870-1931 (Salt Lake City, UT : Project Gutenberg, 2002)
"The Fathers of the Constitution: A Chronicle of the Establishment of the Union" by Max Farrand is a historical account likely written in the early 20th century. The book covers the critical events surrounding the formation of the United States government, focusing on the debates, compromises, and decisions made by the Founding Fathers as they worked to establish a functioning union after gaining independence from Britain. At the start of the book, the author sets the stage by discussing the status of the United States at the conclusion of the Revolution. He explains how, despite the formal recognition of independence from Great Britain, the new nation struggled with issues of legitimacy and respect from other countries. Key figures, including Benjamin Franklin, John Adams, and John Jay, are introduced as influential commissioners involved in negotiating the Treaty of Paris, emphasizing their differing personalities and approaches. The narrative illustrates the challenges faced in achieving international recognition and establishing a cohesive governmental framework during the subsequent years of uncertainty and disunity, highlighting the precarious situation that necessitated the eventual crafting of the Constitution. (This is an automatically generated summary.)
Release date is 2002-01-01
Alev Akman, David Widger and Robert Homa
Keywords: Constitutional history -- United States; United States -- History -- Confederation, 1783-1789; United States -- Politics and government -- 1783-1789